On a Type of Relational Microtoponyms in the Microtoponymy of Zaplanje - Savić, Sandra G. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
This paper examines a specific type of relational microtoponyms within the microtoponymic system of Zaplanje, a region in southeastern Serbia. The study focuses on names structured as a preposition + noun syntagm, as well as compounds formed by a preposition and a noun. Utilizing material collected for a doctoral dissertation, the paper highlights the richness and significance of relational toponyms, illustrating how they enrich the onomasticon of a specific geographical area.The prepositions identified within the recorded naming units include: kod, kraj, na, nad, niz, od, pod, preko, sred, u, and uz. Each preposition combines with a noun to form a syntagm of place functioning in the genitive, accusative, instrumental, or locative case. The most frequent names in the corpus are those expressing spatial relations via the preposition u (21 instances), followed by microtoponyms featuring na and pod. Alongside these prepositional-case syntagms, the analyzed material also comprises prepositional-noun compounds.
Keywords: Zaplanje; toponymy; relational microtoponyms; prepositonal-case constructions; compounds